Soil Transmitted Helminthes In A Rural Population Of Puducherry- A Hospital Based Study - SUNIL SHIVEKAR; PAVAN CHAND; GOPAL RANGASAMY (International Journal of Pharma and Bio Sciences, 2011)
The incidence of soil transmitted helminthic infections was assessed among the patients from a rural part of Puducherry, southern coastal region of India. These patients had attended various outpatient departments in our hospital with various gastrointestinal tract complaints and anemia. Total 2600 patients were screened for parasitic infection over a period of one year (2007-2008) by using standard parasitological techniques. Out of these 417 were positive for parasitic infections of which 286 patients had helminthic infections. Males were more infected than the females. The helminths identified were Hookworm (86.36%), Strongyloides stercoralis (6.29%), Ascaris lumbricoides (2.79%), Trichuris trichiura, (1.04%), Enterobius (1.04%) and Hymenolepis (2.44%)